Associations of GlycA and High-Sensitivity C-Reactive Protein with Measures of Lipolysis in Adults with Obesity - Levine, Jordan A. (J Clin Lipidol, 2020)
BACKGROUND: Obesity-associated inflammation promotes metabolic dysfunction. However, it is unclear how different inflammatory biomarkers predict dysregulation in specific tissues/organs, particularly adipose tissue. OBJECTIVE: The aim of our study was to examine whether GlycA, a nuclear magnetic resonance-measured biomarker of inflammation, is a better predictor of insulin-suppressible lipolysis and other measures of metabolic dysfunction as compared to high-sensitivity C-reactive protein (hsCRP) in human obesity. METHODS: This was a cross-sectional study of 58 non-diabetic adults with obesity (BMI: 39.8±7.0 kg/m(2), age 46.5±12.2y, 67.2% female) who underwent a frequently sampled intravenous glucose tolerance test in the fasted state. Non-insulin-suppressible (l(0)), insulin-suppressible (l(2)), and maximal (l(0)+l(2)) lipolysis rates, as well as insulin sensitivity (S(I)) and acute insulin response to glucose (AIR(G)), were calculated by minimal model analysis. NMR was used to measure GlycA. Body composition was determined by dual-energy X-ray absorptiometry. RESULTS: GlycA was strongly correlated with hsCRP (r=+0.46; p<0.001). GlycA and hsCRP were positively associated with l(2), l(0)+l(2), and fat mass (p’s<0.01). In linear regression models accounting for age, race, sex, and fat mass, GlycA remained significantly associated with l(2) and l(0)+l(2) (p’s<0.05), whereas hsCRP did not (p’s≥0.20). Neither GlycA nor hsCRP were associated with l(0,) S(I) or AIR(G). CONCLUSIONS: GlycA was associated with elevated lipolysis, independent of adiposity, in adults with obesity. Our findings suggest that GlycA and hsCRP have distinct inflammation-mediated metabolic effects, with GlycA having a greater association with adipose tissue dysfunction. Further studies are warranted to investigate the mechanisms underlying these associations.